2016
DOI: 10.1093/nar/gkw1134
|View full text |Cite
|
Sign up to set email alerts
|

OUP accepted manuscript

Abstract: Since its 2001 debut, the University of California, Santa Cruz (UCSC) Genome Browser (http://genome.ucsc.edu/) team has provided continuous support to the international genomics and biomedical communities through a web-based, open source platform designed for the fast, scalable display of sequence alignments and annotations landscaped against a vast collection of quality reference genome assemblies. The browser's publicly accessible databases are the backbone of a rich, integrated bioinformatics tool suite tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
163
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(163 citation statements)
references
References 49 publications
0
163
0
Order By: Relevance
“…Data culled from chromatin immunoprecipitation sequencing (ChipSeq) experiments 20 demonstrated that the progesterone receptor binds directly to the PDK4 promoter as well as a region approximately 10kb upstream, and receptor binding was markedly increased by the presence of progesterone (Online Figure IVF). ENCODE data 21 demonstrates that both of these regions are hypersensitive to DNAseI digestion, and contain a high amount of histone acetylation at H3K27, indicating high transcriptional regulatory activity at both sites. Both regulatory sites contain strong candidate progesterone-binding sequences 22 (Online Figure IVF), consistent with the observed progesterone receptor binding.…”
Section: Resultsmentioning
confidence: 99%
“…Data culled from chromatin immunoprecipitation sequencing (ChipSeq) experiments 20 demonstrated that the progesterone receptor binds directly to the PDK4 promoter as well as a region approximately 10kb upstream, and receptor binding was markedly increased by the presence of progesterone (Online Figure IVF). ENCODE data 21 demonstrates that both of these regions are hypersensitive to DNAseI digestion, and contain a high amount of histone acetylation at H3K27, indicating high transcriptional regulatory activity at both sites. Both regulatory sites contain strong candidate progesterone-binding sequences 22 (Online Figure IVF), consistent with the observed progesterone receptor binding.…”
Section: Resultsmentioning
confidence: 99%
“…Significance of predicted folding stability was assessed by shuffling the original sequence 10,000 times while preserving dinucleotide frequency (Jiang et al, 2008), computing the fold and Δ G for each shuffled sequence, and then designating the empirical P value as the fraction of shuffled sequences with the same or lower predicted Δ G . Covariations in the CENPB 3′-end structure were detected by RNAalifold (Lorenz et al, 2011), using a multiple sequence alignment of 62 mammalian species downloaded from UCSC Table browser (Tyner et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Somatic Mutation Datasets and Protein–Protein Interaction Datasets : Six nonsilent somatic mutation (nonsense mutations, missense mutations, frame‐shift indels, splice site mutations, or stop codon read‐throughs) datasets of Pan‐Cancer (namely, AWG, bcgsc, bcm, broad, ucsc, and wustl) and 19 datasets of individual cancer types were collected from the TCGA database by UCSC Browser42 (https://xenabrowser.net/datapages/) (Tables S1 and S2, Supporting Information). Two independently developed PPI datasets HumanNet24 and STRINGv1025 were downloaded from their respective websites.…”
Section: Methodsmentioning
confidence: 99%